2022
DOI: 10.3390/jimaging8100277
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Liver Disease Using MRI-Based Radiomic Features of the Liver and Spleen

Abstract: Background: Radiomics extracts quantitative image features to identify biomarkers for characterizing disease. Our aim was to characterize the ability of radiomic features extracted from magnetic resonance (MR) imaging of the liver and spleen to detect cirrhosis by comparing features from patients with cirrhosis to those without cirrhosis. Methods: This retrospective study compared MR-derived radiomic features between patients with cirrhosis undergoing hepatocellular carcinoma screening and patients without cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Yin et al found out that machine learning models incorporating CT splenic features outperformed models solely considering CT hepatic features when detecting the liver fibrosis stage [ 33 ]. A similar approach was followed by Sack et al [ 28 ], who combined MRI liver and spleen radiomic features to detect cirrhosis, and by Nitsch et al [ 26 ], who developed a predictive model of disease severity for cirrhosis compared with the existing MELD (Model for End-Stage Liver Disease) score.…”
Section: Discussionmentioning
confidence: 99%
“…Yin et al found out that machine learning models incorporating CT splenic features outperformed models solely considering CT hepatic features when detecting the liver fibrosis stage [ 33 ]. A similar approach was followed by Sack et al [ 28 ], who combined MRI liver and spleen radiomic features to detect cirrhosis, and by Nitsch et al [ 26 ], who developed a predictive model of disease severity for cirrhosis compared with the existing MELD (Model for End-Stage Liver Disease) score.…”
Section: Discussionmentioning
confidence: 99%
“…4 [93] successfully used conventional MRI and clinical data with machine learning algorithms to reconstruct virtual MR enterography images for assessing liver stiffness and the fibrosis category. Sack et al [94] found that MR-based liver and spleen radiomic features were highly accurate in identifying cirrhosis.…”
Section: Application Of Ai Based On Ctmentioning
confidence: 99%
“…Sack et al. [94] found that MR‐based liver and spleen radiomic features were highly accurate in identifying cirrhosis.…”
Section: Artificial Intelligence Based On Imaging For Diffuse Liver D...mentioning
confidence: 99%